Antagonism between abscisic acid and gibberellin regulates starch synthesis and corm development in Gladiolus hybridus. (1st July 2021) - Li, Jingru; Seng, Shanshan; Li, Donglei; Zhang, Fengqin; Liu, Yixuan; Yao, Ting; Liang, Jiahui; Yi, Mingfang; Wu, Jian
Abstract: Understanding corm development in flower bulbs is of importance for securing the quality of cut flowers and propagation of commercial stocks. Gladiolus is one of the most popular bulb plants worldwide. Its corm development is characterized by starch accumulation. Previous research has shown that phytohormones (especially gibberellin (GA)) are involved in tuber development. However, the relationship between abscisic acid (ABA)/GA and starch during corm development remains unclear. To gain deeper insights into the biological process of corm development, we performed a detailed anatomical characterization of different stages of corm development and analyzed phytohormone levels. Our study showed that corm development is linked to hormones (ABA and GA) and carbohydrates (sucrose and starch). Exogenous hormone treatment and silencing of endogenous hormone biosynthesis genes indicated that ABA positively regulates corm development, while GA acts as an antagonist of ABA function. A sucrose synthase gene ( GhSUS2 ) was shown to be involved in the antagonism between ABA and GA. GhSUS2 was upregulated by ABA and downregulated by GA. The increase in the transcript level of GhSUS2 coincided with the development of corm/cormels. Silencing of GhSUS2 repressed corm development and starch accumulation. In conclusion, we propose that GhSUS2, an essential enzyme in sucrose degradation, is differentially regulated by ABA and GA and controls corm development in Gladiolus.